2017
DOI: 10.14419/ijm.v5i1.7152
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the delay in seeking first antenatal care service among pregnant women at Katutura state hospital, Khomas region

Abstract: The purpose of this study was to identify the factors associated with the delay in seeking first antenatal care (ANC) service among pregnant women at Katutura state hospital, Khomas region. A qualitative, explorative and descriptive design was used to gain the data from pregnant women started first antenatal care later than twelve weeks of gestation. Data was collected through in-depth interview among pregnant women during their first visit at Katutura state hospital antenatal clinic, Khomas region. The data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In Kyenjojo General Hospital, the maternal mortality is very high at 750 per 100,000 live births [9]. It is also indicated that ANC attendance in the region has remained very low at (50%) despite the fact that WHO recommends eight ANC contacts during pregnancy (Kasule et al 2013) [11].…”
Section: Background Of the Studymentioning
confidence: 99%
“…In Kyenjojo General Hospital, the maternal mortality is very high at 750 per 100,000 live births [9]. It is also indicated that ANC attendance in the region has remained very low at (50%) despite the fact that WHO recommends eight ANC contacts during pregnancy (Kasule et al 2013) [11].…”
Section: Background Of the Studymentioning
confidence: 99%
“…Many pregnant women in sub-Saharan Africa start their first antenatal care attendance late, mostly in the second and third trimester[3, 9]. Thus, late antenatal attendance makes difficult to implement effectively the routine ANC strategies that enhance maternal wellbeing and good prenatal outcomes [1012].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study by Komuhangi et al, there was no statistically significant relationship between age, marital status and late booking but there was significant relationship between level of education, religion, parity and late booking. 7,26 This was a retrospective study where only the information in medical records were used.…”
Section: Nonye-enyidahmentioning
confidence: 99%